PEMANFAATAN E-COMMERCE DALAM PENERIMAAN PAJAK - Munthe, Desi Triana (JURNAL PERPAJAKAN, 2024)
Indonesia's tax revenue in 2012 was still under budget. The increase in the number of taxpayers every year is still not able to cover the deficit. Ecommerce, which continues to grow in number every year, can be one of the right solutions to solve this problem. One of the factors that can affect e-commerce is Indonesian internet users which are also increasing every year. Unfortunately, the Directorate General of Taxes has still not decided on the perfect regulations for e-commerce transactions in Indonesia. Indonesia needs to define which transactions should be taxed. This study aims to determine the potential tax revenue from e-commerce transactions in Indonesia.